Magnetic Resonance Imaging of Lumbar Spine in Lower Backache: A Comparative Study on Gender Basis - Nazia Azeem; Muhammad Anwar; Shazia Kadri (Journal of Bahria University Medical and Dental College)
Objective: To compare the clinical features of lower backache with Magnetic Resonance Imaging (MRI) findings on gender basis. Study design & Setting: A cross-sectional descriptive study was carried out among male & female patients with a backache at Sir Syed Hospital, Karachi. This study conducted from 1st Jan 2020 to 1st June 2020. We studied 90 patients by using the non-probability convenient sampling technique. Methodology: Lower backache is a common problem that creates disability. MRI lumbar spine without contrast were reviewed with clinical complaints. Performa was used after the ethical approval from Institutional Research and Ethical committee. Components focused during the study in MRI findings at different spinal levels were disc bulging, neural foraminal compromise, nerve root compression, ligamentum flavum and facet joint hypertrophy. Results: The results showed that the mean age of 90 patients was 44.64 years. On MRI imaging 46(86.8%) males and 26(70.3%) females had disc desiccation but multi-level disc osteophyte complexes were demonstrated more in females 11(29.7%). Diffuse disc bulge is more in males at L4-5 and L5-S1 level 49(92.5%) than in females 34(91.9%) at L4-5 and 33(89.2%) at L5-S1 level with mild to moderate spinal canal stenosis. The narrowing of Neural foramen is almost similar at L4-5 level in both gender but more at L5-S1 in females 35(94.6%) as compared to males 49(92.5%) with nerve root compression. Overall male patients tended to have slightly more disc degenerative changes than females.